2013
DOI: 10.1213/ane.0b013e318279b37a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 4 Airway Devices on Cervical Spine Alignment in Cadaver Models of Global Ligamentous Instability at C1-2

Abstract: Background The effects of advanced airway management on cervical spine alignment in patients with upper cervical spine instability are uncertain. Methods To examine the potential for mechanical disruption during endotracheal intubation in cadavers with unstable cervical spines, we performed a prospective observational cohort study with three cadaver subjects. We created an unstable, type II odontoid fracture with global ligamentous instability at C1-2 in lightly embalmed cadavers, followed by repetitive intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Recently, two cadaver intubation studies utilized an electromagnetic motion analysis device to simultaneously quantify intervertebral rotations and translations in the sagittal plane (flexion – extension), coronal plane (lateral bending), and axial plane (axial rotation). 31,32 These studies showed that, during intubation, angulation occurred in all three planes, but that sagittal motion (extension) was the greatest. 31,32 This observation is consistent with other clinical studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, two cadaver intubation studies utilized an electromagnetic motion analysis device to simultaneously quantify intervertebral rotations and translations in the sagittal plane (flexion – extension), coronal plane (lateral bending), and axial plane (axial rotation). 31,32 These studies showed that, during intubation, angulation occurred in all three planes, but that sagittal motion (extension) was the greatest. 31,32 This observation is consistent with other clinical studies.…”
Section: Discussionmentioning
confidence: 97%
“…31,32 These studies showed that, during intubation, angulation occurred in all three planes, but that sagittal motion (extension) was the greatest. 31,32 This observation is consistent with other clinical studies. 33 In in vitro isolated spinal segments, flexion/extension is the most sensitive load direction for disco-ligamentous instability.…”
Section: Discussionmentioning
confidence: 97%
“…Lightwand is a rapid, effective, and safe tool for facilitating intubation in patients with difficult airway and in patients required for minimal neck movements through transillumination in the neck [14,19]. Whether lightwand-guided technique can also be used for guiding real-time insertion of the cLMA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine trauma tends not to be isolated to simply a fracture site. Ligamentous injury [5], surrounding tissue oedema and haematoma formation all play a role in the trauma patient. Transection of the cord or contusion during airway manipulation may also be important.…”
mentioning
confidence: 99%